Evaluation in basic education in times of pandemic and the guidelines of ordinance 4.904/2020-Alagoas - Silva, Jakeline Vieira da; Silva, José Washington Vieira; Duarte, Madileide de Oliveira (Seven Editora, 2023)
The pandemic in 2020 greatly compromised teaching and learning in basic education. Teachers and students had to adapt to a new reality that caused several obstacles in daily school life. The consequences of the evaluation were even greater. New procedures based on Ordinance No. 4,904/2020 of the government of Alagoas gave the north to the teaching actions. Given this reality, the research problem related to reports in elementary and high school: 1) With remote teaching in 2020, what strategies did the teacher use to achieve a quality formative assessment among students? 2) Based on Art. 3 of Ordinance 4.904/2020, what challenges can the teacher overcome in the evaluation process? General objective: to reflect on strategies used for formative evaluation in pedagogical practice in Basic Education, during the pandemic, in the year 2020. Methodology: reports of experience of teaching actions about the evaluation of students in elementary and secondary education. Theoretical contributions: Legislation - Alagoas (2020), Brazil (2018). Readings by: Vieira Silva; Duarte (2018), Hoffmann (2014), Demo (2004), Freire (1996), Sant’anna (1995), Gatti (1993) among others. Lives: Gatti, Hoffmann (2020); Nóvoa (2021). Results achieved: evaluation with the support of technological resources, Google Meet, WhatsApp, Google Play Games for the realization of explanations, biweekly scripts printed with corrections and return for the student in elementary school. Youtube, Google Classroom, Google Forms, Padlet, Jambord, and Google Meet, among others, in high school. At both levels, the support of Ordinance 4.904/2020/Alagoas favored the referrals of teachers in the conduct of online teaching work. Even so, some students were impaired in learning and, consequently, in the evaluation because they did not have access to computers and the internet, both in elementary school and high school. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-033